Gold(III)-catalyzed formal [3 + 2] annulations of N-Acyl sulfilimines with Ynamides for the synthesis of 4-Aminooxazoles - Tian, Xianhai; Song, Lina; Han, Chunyu; Zhang, Cheng; Wu, Yufeng; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Organic letters, 2019)
A gold-catalyzed formal 1,3-dipolar [3 + 2] annulation using readily accessible N-acyl sulfilimines and ynamides is reported. This reaction includes the cleavage of a N-S bond and subsequent C-O bond formation. In total, 30 oxazole derivatives bearing diverse functionalities could be prepared in 43-98% yield from the corresponding sulfilimines and ynamides.